Cerebral cavernous malformations: from CCM genes to endothelial cell homeostasis - Fischer, Andreas; Zalvide, Juan; Faurobert, Eva; Albiges-Rizo, Corinne; Tournier-Lasserve, Elisabeth (Trends in molecular medicine, 2013)
Cerebral cavernous malformations (CCMs) are vascular lesions that can occur sporadically or as a consequence of inherited loss-of-function mutations, predominantly in the genes CCM1 (KRIT1), CCM2 (MGC4607, OSM, Malcavernin), or CCM3 (PDCD10, TFAR15). Inherited, familial CCM is characterized by the development of multiple lesions throughout a patient's life leading to recurrent cerebral hemorrhages. Recently, roles for the CCM proteins in maintaining vascular barrier functions and quiescence have been elucidated, and in this review we summarize the genetics and pathophysiology of this disease and discuss the molecular mechanisms through which CCM proteins may act within blood vessels.
Gesehen am 06.04.2021